2001
DOI: 10.1164/ajrccm.164.5.2007034
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Failure Following HAART Introduction in Patients Treated for Pneumocystis carinii Pneumonia

Abstract: Cases of paradoxical worsening of opportunistic infections shortly after the beginning of highly active antiretroviral therapy (HAART) prompted questions on the optimal timing of introduction of HAART in patients with inaugural AIDS-related opportunistic infections. We describe three cases of acute respiratory failure after early introduction of HAART in patients treated for Pneumocystis carinii pneumonia (PCP). The three patients had severe PCP that initially improved with anti-PCP and adjunctive steroid ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
1
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 17 publications
6
70
1
4
Order By: Relevance
“…It has also been reported that there is paradoxical worsening of PCP in patients started on highly active antiretroviral therapy. 54 Clinical and experimental studies have shown that inflammatory injury is a major cause of morbidity and mortality associated with PCP, potentially due to a more robust immune response to pulmonary microorganisms. We found that immune dysregulation triggered by SIV and P. carinii, and increased expression of IFN-␥, and CXCR3 and CCR5 ligands are associated with these inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that there is paradoxical worsening of PCP in patients started on highly active antiretroviral therapy. 54 Clinical and experimental studies have shown that inflammatory injury is a major cause of morbidity and mortality associated with PCP, potentially due to a more robust immune response to pulmonary microorganisms. We found that immune dysregulation triggered by SIV and P. carinii, and increased expression of IFN-␥, and CXCR3 and CCR5 ligands are associated with these inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in patients with PCP, cART needs to be started before completion of the acute phase of anti-P. jiroveci treatment to avoid any possible complication of the clinical picture [52] (B-III). It is important that if there is either evidence of clinical worsening or a lack of response to etiologic treatment, cART should be started during the first 14 days (C-III).…”
Section: (C-i)mentioning
confidence: 99%
“…11,12 These types of interactions may be relevant in immune reconstitution disease (IRD), which occurs in some AIDS patients in whom highly active anti-retroviral therapy results in markedly increased levels of CD4 lymphocytes. In some of these individuals, intense inflammatory responses can occur in the lungs (involving CD4 cells and residual Pneumocystis organisms 13,14 ) and requires vigorous therapeutic intervention. This clinical syndrome highlights the potential interaction of multiple inflammatory cell types and mechanisms that may be involved in the pathology of PCP.…”
mentioning
confidence: 99%